SimTwo realistic simulator: a tool for the development and validation of robot software - Costa, Paulo Gomes da (2011)
Many times the simulation environment is an ad hoc implementation done with the single purpose of testing the author's algorithm or methodology. It is not difficult to find that the accuracy of the simulation is low and mostly unable to reflect the real world. While, under certain circumstances, that can be a valid approach there is the need of a simulation environment where the focus is on the physical realism while retaining a lot of configurability so that it can be adapted to a lot of different uses. In this paper it is presented a simulation environment where multiple kinds of robots can be modeled. The robots can be modeled based on a network of physical bodies interconnected by joints that can be powered, or not, by electrical motors. The corresponding low level controllers and the high level decision or IA can also be implemented in the simulation environment. To achieve that, some established open source libraries like the Open Dynamics Engine are used. The parameters for the physical simulation are all accessible when defining the robot model and a very accurate motor model can also be implemented. There is also the ability to use external modules to implement the high level controllers.